Georgia's Aspiration Towards EU Integration: A Pathway to Economic and Social Prosperity - Veshapidze, Shota (Ivane Javakhishvili Tbilisi State University Press, 2025)
Georgia’s aspiration to integrate into the European Union (EU) is a significant factor that is transforming the country’s political landscape and improving its economic and social well-being. This article examines Georgia’s path towards EU integration, analyzing its economic, social and political reforms against the backdrop of EU standards. By examining the strategic benefits and challenges of integration, the study aims to understand the multifaceted nature of EU-Georgia relations, highlighting the opportunities and obstacles that lie ahead. As Georgia continues to strengthen its ties with Europe, EU integration is seen as a path to economic modernization, democratic development, and regional stability, making it a key area for Georgia’s future. The aim of this article is to assess Georgia’s progress towards EU integration by examining how this trajectory can enhance its economic and social development, as well as its potential to overcome the challenges of the process. It focuses on Georgia’s EU integration process, specifically examining the economic, political, and social consequences of EU membership. It examines the strategies, policies, and institutional changes needed for successful integration. The object of the study is the process of Georgia's integration into the European Union, with a particular focus on its economic reforms, social transformation and compliance with EU standards. The study uses qualitative and quantitative methods, including a review of policy documents, EU reports and academic articles. Comparative analysis is used to assess the experiences of other Eastern European countries in the process of joining the EU. The practical significance of this work lies in its potential to inform policymakers, international organizations, and Georgian citizens about the benefits and challenges of EU integration. It provides a comprehensive analysis of the necessary reforms and strategic decisions needed to ensure Georgia's smooth and successful accession to the EU. The conclusion is that Georgia’s European integration is a complex and dynamic process that delivers significant economic and social benefits. However, the path to membership requires significant reforms, sustained political will, and active participation of Georgian citizens. Georgia, if it successfully advances its EU accession process, could serve as an example for other countries in the region aspiring to European integration.
1. Bedianashvili, G. (2018). Culture as a Factor in the Formation of the Knowledge Economy with the Systemic and Institutional Context of Paradigmatic Changes. Globalization and Business. 6, 58-66. DOI: 10.35945/ gb. 2018.06.007 6 2. Bedianashvili, G. (2021). Macroeconomic and cultural determinants of the covid-19 pandemic crisis. Bulletin of the Georgian National Academy of Sciences. 15(2):191-197.CAP 2023-2027. https://agriculture.ec.europa.eu/ common-agricultural-policy/cap-overview/cap-2023-27/key-policy-objectives- cap-2023-27_en 3. Fontaine, P. (2014). How the European Union Works: 12 Lessons About Europe. Brussels. 4. Garakanidze, Z; Bilynska, M. (2024). Exploring Individual Resilience as A Component of National Resilience In Ukraine During The Wartime. Business-Engineering, N3-4, 2024. pp.11-16; https://business engineering. bpengi. com/home/2024/number-03-04; 5. Garakanidze, Z; Bilynska, M. (2024). Possible New Role of the GTS (Ukraine) for the EU Energy Security. Bucharest, Romania. https://www.geopolitic. ro/2024/09/possible-new-role-gts-ukraine-eu-energy-security/; 6. Garakanidze, Z., Garakanidze, N. (2018). Ekonomichnyj separatyzm ta joho vyiavlennia [Economic Separatism and its Detection]. Bulletin of the NAPA, Series “Рublic Аdministration”,3 (90), 2018, Kiev, Ukraine. pp. 32-42; http:// visnyk.academy.gov.ua/pages/dop/81/files/1c61030f-cfd0-49b0-b853-32e88ee63f54.pdf. 7. Garakanidze, Z. and Pavliashvili, S., 2024. Demonopolization of the EU Gas Market in the Conditions of the Russia-Ukraine War. Economics & Business (1987-5789), (2). 8. Gvelesiani, M., Veshapidze, S. (2016). European Values: What Can WeImplement from Them and How Can We Implement Them in Georgia. “Globalization & Business”. (1). 40-46. (In Georgian). 9. Gvelesiani, M., Veshapidze, S. (2016). Values: Limits and Contradictions. Globalization & Business, (1). 35-39. (In Georgian). 10. Jamagidze, L. (2016). B/Orders and Economic Integration Preferences: The Case of Georgia. Ecoforum Journal, 5(3). 11. Jamagidze, L. (2022). Georgia-Romania Economic Cooperation and the New Regional Challenges. EURINT, 9(1), 133-150. 12. Karchava, L., 2018. Theoretical basics of business communication and Its connection with other sciences/ბიზნესკომუნიკაციების თეორიული საფუძვლები და მისი კავშირი სხვა მეცნიერებებთან. The New Economist, 13(3), pp.69-2. (In Georgian). 13. Karchava, L., Veshapidze S., Chiabrishvili, K. (2023). Economic Perspective of Establishing Strategic Partnership Between China And Georgia. DOI suffix: 10.36962/NEC18032023-7. The New Economist N 3 (2023), Vol 18, Issue 3 (In Georgian). 14. Karchava, L., Veshapidze, S., & Tsikelashvili, S. (2025). Georgia's Perspective in the Context of Developing Economic Relations between China and the European Union. The New Economist, 20(1), 8-23. 15. Kozak, Y., Shengelia, T., & Gribincea, A. (2014). International economic relations. Kiev-Katowice: CUL. 16. Lomia, T. and Lomia, E., 2020. Economic and Political Support of the European Union to Georgia: Retrospective Analysis of the EU-Georgia Relations. Vallis Aurea, 6(1), pp.35-43. 17. Lomia, E., 2021. CHINA’S BELT AND ROAD INITIATIVE AND GEORGIA: A SHORT OVERVIEW. Journal of Liberty and International Affairs, 7(3), pp.373-385. 18. Lomia, E. and Karchava, L., 2021. Georgian ethnopolitical conflict as a subject of confrontation between the USA and Russia. Journal of Liberty and International Affairs, 7(2), pp.90-102. 19. Lomia, E. and Lomia, T., 2021. EU Policy in the South Caucasus Region and Georgia's Participation in the European “Neighborhood Policy” and the “Eastern Partnership” programmes/European Union policy in the South Caucasus region and Georgia's participation in its programs. The New Economist, 16(1), pp.62-2. 20. Papava, V. (2016). Georgia’s Choice: the European Union or the Eurasian Economic Union. GFSIS, Expert Opinion, 57, https://gfsis.org.ge/files/library/ opinion-papers/57-expert-opinion-eng.pdf. 21. Papava, V. (2020). Becoming European: Challenges for Georgia in the Twenty-First Century. iUniverse. Bloomington. 22. Papava, V. (2020). Georgia’s European Way During the Period of Pandemic Deglobalization. Rondeli Blog, August 6, https://gfsis.org.ge/blog/ view/1091. 23. Papava, V. (2022). Pandemic, War and Economic Sanctions: From Turbulent to Confrontational Globalization. Eurasia Review, May 23, Available at: https://www.eurasiareview.com/23052022-pandemic-war-and-economic- sanctions-from-turbulent-to-confrontational-globalization-oped/. 24. Papava, V. (2022). On Economic Growth in the G20 Countries in 2022, Adjusted for the Catch-Up Effect. Eurasia Review, August 4. Available at: https:// www.eurasiareview.com/04082022-on-economic-growth-in-g20-countriesin- 2022-adjusted-for-catch-up-effect-analysis/. 25. Papava, V. (2022). On the Main Challenges of the Architecture Transformation of the World Economy. Eurasia Review, March 31, Available at: https:// www.eurasiareview.com/31032022-on-the-main-challenges-of-the-architecture-transformation-of-the-world-economy-oped/?fbclid=IwAR1Q-caff-Bi-PLQh121S5SVHxXZiJG0ALCBAiSptdq5pNjduMmqtZPvcal0 26. Papava, V. (2022). Pandemic, War and Economic Sanctions: From Turbulent to Confrontational Globalization. Eurasia Review, May 23, https:// www.eurasiareview.com/23052022-pandemic-war-and-economic-sanctions-from-turbulent-to-confrontational-globalization-oped/. 27. Papava, V. (2022). On Sanctionomics. Eurasia Review, March 14. Available at: https://www.eurasiareview.com/14032022-on-sanctionomics-oped. 28. Papava, V. (2022). Cold War vs. Hot War in 2022. Eurasia Review, February 28. Available at: https://www.eurasiareview.com/28022022-cold-war-vshot- war-in-2022-oped 29. Papava, V., Maisaia, V. (2023). On Economic Security under Confrontational Globalization and the Main Concepts of Geo-Economic Warfare. Bulletin of the Georgian National Academy of Sciences, 17(3), 116-120. 30. Pavliashvili, S. and Tokmazishvili, M., 2024. MODERNIZING FARMERS'EDUCATION IN THE EU: CHALLENGES AND APPROACHES. German International Journal of Modern Science/Deutsche Internationale Zeitschrift für Zeitgenössische Wissenschaft, (82). 31. Pavliashvili, S. and Tokmazishvili, M., 2024. Challenges of farmers' education system in Georgia. Foundations and Trends in Modern Learning, (5). 32. Pavliashvili, S. and Garakanidze, Z., 2024. The Impact of the Russia-Ukraine War on the EU Gas Spot Market. Economics & Business (1987-5789), 16(1). 33. Pavliashvili, S. and Tokmazishvili, M., 2024. GLOBAL ECONOMIC AND LEGAL PROBLEMS OF INTRODUCING THE CIRCULAR ECONOMY AND GEORGIA. Norwegian Journal of development of the International Science No, 145, p.51. 34. Pazhava, E. (2022). The Genesis of Georgia's European Orientation, Tbilisi. 284 p. https://rustaveli.org.ge/res/docs/01dfe51cdde44c1dab1be9 a853b640a75a36ed88.pdf 65. (In Georgian).. 35. Putkaradze, R. (2015). Historical Aspects of Trade and Economic Relations between Georgia and the European Union. ZeszytyNaukowe UNIWERSYTETU PRZYRODNICZO-HUMANISTYCZNEGO w SIEDLCACH Seria: AdministracjaiZarządzanie. Scientific Journal, Nr 107. pp. 97-105 36. Putkaradze, R. (2018). Pressing Issues of Economic Integration of Croatia And Georgia. Науковий журнал. ВІСНИК. Scientific journal, HERALD. Of Khmelnytskyi National University, Economic sciences, Issue 5, Part 1 (262). 37. Putkaradze, R. (2018). Trade Relations Between Georgia And The European Union After Signing The Association Agreement. South East European University. 2nd International Scientific Conference on Business and Economics. May 25. conf.seeu.edu.mk. CONFERENCE PROCEEDINGS. Tetovo, Republic of Macedonia. p. 183-188. 38. Putkaradze, R. (2019). Georgia in the European Union’s Eastern Partnership Countries: Historical Aspects and Challenges. Journal, Ecoforum Journal. Volume 8, Issue 1(18). 39. Rodrik, D. (2022). Beware Economists Bearing Policy Paradigms, May 11, 2021. https://www.project-syndicate.org/commentary/economic-policy-must-abandon-universal-paradigms-by-dani-rodrik-2021-05 40. Rodrik, D. (2021). Beware Economists Bearing Policy Paradigms. Project Syndicate. 41. Sepashvili, E. (2014). Political and economic aspects of security policy in relation to Eastern Partnership: perspectives for Georgia. FROM CAPACITIES TO EXCELLENCE, 17. 42. Sepashvili, E. (2017). Eastern Partnership Integration with the EU and Inclusive Growth of National Economies. Management Dynamics in the Knowledge Economy, 5(3), 439-453. 43. Sichinava, A., Chikava, M., Veshapidze, S., Sekhniashvili, D., & Pailodze, N. (2013). Realities of internationalization of higher education in Georgia. In PRADEC Conference Proceedings (Vol. 2, No. 1, pp. 95-98). 57. Shaburishvili, S. (2011). Peculiarities of Georgian Foreign Trade with the European Union. Bulletin of Khmelnitsky National University, 2, 252-254. 44. Shengelia, T. (2018). Social Capital of Dominant Ethnic Groups and Its Impact on Business. 45. Shengelia, T. (2019). Research methodology and the impact of social entrepreneurship on the solution of social problems in Georgia. 46. Shengelia, T., & Gelashvili, M. (2020). Export potential of Georgia. In World economy and international economic relations (Vol. 3, pp. 29-33). 47. Shengelia, T., Kozak, Y., & Kirkitadze, Z. (2020). FDI motivation effects on Host countries. In World economy and international economic relations (Vol. 3, pp. 15-20). 48. Shengelia, T., Berishvili, K., Jganjgava, K. (2022). Improving the Methodology of Measuring Social Capital in International Companies. Sciences of Europe, (97), 15-18. 49. Silagadze, A. (2022). Contemporary Global Economic Trends: Transitional Economies during Covid-Depression Bull. Georg. Natl. Acad. Sci, 16(3), 130-135 50. Silagadze, A. (2011). Economic Teachings, Ilia Chavchavadze and Modernity- “Actual problems of Historical and economic Teachings “. “VZFEI”, pp.71 -77. 51. Silagadze, A. (2018). Gini Index–Wealth Distribution in the Post-Soviet Countries. Bulletin Of The Georgian National Academy Of Sciences, vol. 12, no.3.193 52. Silagadze, A. (2022). Economics Contemporary Global Economic Trends: Transitional Economies during Covid-Depression. Bulletin Of The Georgian National Academy Of Sciences, vol. 16, no. 3, p. 130–135. 53. Silagadze, A., Atanelishvili, T. (2010). Aspects of Economic Doctrines in Georgia. Peninsula University of Technology, Business and Informatics. San Francisco (USA). 54. Silagadze, A., Atanelishvili T., Silagadze N. (2022). Covid Depression and Search for a New Paradigm. Bulletin of The Georgian National Academy of Sciences,16(1): 121-125. 55. Silagadze, A., & Zubiashvili, T. (2015). Parametrs of the European Union and the post-soviet Georgia's economy. International Journal of Multidisciplinary Thought, 5(3), 441-448. 56. Veshapidze, S. (2017). The Traditions Orientated on European Values In Georgia. Sciences of Europe, (13-4), 14-18. 57. Shaburishvili, S. (2011). Peculiarities of Georgian Foreign Trade with the European Union. Bulletin of Khmelnitsky National University, 2, 252-254. 58. Shengelia, T. (2017, July). Determination of correlative relations between social capital, trust and motivation in the international company. In Proceedings of Business and Management Conferences (No. 5607685). International Institute of Social and Economic Sciences. 59. Shengelia, T. (2018). Social Capital of Dominant Ethnic Groups and Its Impact on Business. 60. Shengelia, T. (2019). Research methodology and the impact of social entrepreneurship on the solution of social problems in Georgia. 61. Shengelia, T., & Gelashvili, M. (2020). Export potential of Georgia. In World economy and international economic relations (Vol. 3, pp. 29-33). 62. Shengelia, T., Kozak, Y., & Kirkitadze, Z. (2020). FDI motivation effects on Host countries. In World economy and international economic relations (Vol. 3, pp. 15-20). 63. Shengelia, T., Berishvili, K., Jganjgava, K. (2022). Improving the Methodology of Measuring Social Capital in International Companies. Sciences of Europe, (97), 15-18. 64. Silagadze, A. (2022). Contemporary Global Economic Trends: Transitional Economies during Covid-Depression Bull. Georg. Natl. Acad. Sci, 16(3), 130-135 65. Silagadze, A. (2011). Economic Teachings, Ilia Chavchavadze and Modernity- “Actual problems of Historical and economic Teachings “. “VZFEI”, pp.71 -77. 66. Silagadze, A. (2018). Gini Index–Wealth Distribution in the Post-Soviet Countries. Bulletin Of The Georgian National Academy Of Sciences, vol. 12, no.3.193 67. Silagadze, A. (2022). Economics Contemporary Global Economic Trends: Transitional Economies during Covid-Depression. Bulletin Of The Georgian National Academy Of Sciences, vol. 16, no. 3, p. 130–135. 68. Silagadze, A., Atanelishvili, T. (2010). Aspects of Economic Doctrines in Georgia. Peninsula University of Technology, Business and Informatics. San Francisco (USA). 69. Silagadze, A., Atanelishvili T., Silagadze N. (2022). Covid Depression and Search for a New Paradigm. Bulletin of The Georgian National Academy of Sciences,16(1): 121-125. 70. Silagadze, A., & Zubiashvili, T. (2015). Parametrs of the European Union and the post-soviet Georgia's economy. International Journal of Multidisciplinary Thought, 5(3), 441-448. 71. Ukleba M., Tsikhelashvili M. (2022). South Caucasus – European Union Relations in the Context of Economic Development. https:// di.gov.ge/publications/analytical-papers/samkhrethi-kavkasia-evrokavshirisurthierthobebi- ekonomikuri-ganvitharebis-tcrilshi-mikheil-ukleba-mamukacikhelashvili/ (In Georgian). 72. Veshapidze, S. (2017). The Traditions Orientated on European Values In Georgia. Sciences of Europe, (13-4), 14-18. 73. Veshapidze, S., Babuadze, N., & Beridze, T. (2015). Nobel Prize Laureate in Economy Simon S. Kuznets About Actual Problems of a Sustainable Development of National Economy. In Materials of reports made at the international scientific-practical conference held at Paata Gugushvili Institute of Economics of Ivane Javakhishvili Tbilisi State University in (p. 79). 74. Veshapidze, S., Bakhtadze, L., Putkaradze, R., Kharitonashvili, J., Danelia, I., Lominashvili, M., & Chantladze, N. (2024). Modern international economic relations of Georgia. (In Georgian). 75. Veshapidze, S., Chiabrishvili, K., Zubiashvili, T., Zoidze, G. (2021). On the Relationship between Education and Economic Security. Ecoforum Journal, 10(3). 76. Veshapidze, S., Karchava, L. (2022). Contradictions of Globalization under the COVID-19 Pandemic. Bulletin of the Georgian National Academy of Sciences, 16(4), 152-157. 77. Veshapidze, S., Kitashvili, S. (2024). Georgia’s European Integration Perspective. Ekonomisti. 2 (XX), 94-112 p ISSN 1987-6890 e ISSN 2346-8432. (In Georgian). 78. Veshapidze, S., Kitashvili, S. (2025). The Importance and Benefits of the EU single market for Georgia. The New Economist, 19(3), 60-73. (In Georgian). 79. Veshapidze, S., Kereselidze, L., Tsirdava, N. (2024). Decarbonization of Energy and Challenges of Sustainable Development of Georgia. Ekonomisti 4. P ISSN 1987-6890 e ISSN 2346-8432. (In Georgian). 80. Veshapidze, S., Megreladze, G. (2024). Prospects for the development of Georgia’s trade with the European Union. The New Economist, 19(2), 11-223. ISSN 1512-4649(Print) ISSN 2667-9752(Online). (In Georgian). 81. Veshapidze, S., Otinashvili, R., Gvarutsidze, A., Abuselidze, G., Zoidze G. (2022). Modern Technologies to Overcome the Challenges of Globalization. Entrepreneurship. Volume: 10, Number: 2.https://www.ceeol.com/search/article- detail?id=1074987 82. Veshapidze, S., Zoidze, G. (2022). Value Choices of the Community in the Context of the COVID-19 Pandemic. DOI: https://doi.org/10.5281/zenodo. 6373197 83. Veshapidze, S., Zoidze, G., Berishvili, K. (2021). The Economic Determinant of the Education System. Sciences of Europe, (81-2), 6–12. DOI: https:// doi.org/10.24412/3162-2364-2021-81-2-6-12 84. Veshapidze, S., Zubiashvili, T. (2021). About Population Growth and Global Problems. VI International Scientific Conference: “Challenges of Globalization in Economics and Business”, Tbilisi, 2021, pp. 148-155 85. Veshapidze, S., Zubiashvili, T., Chiabrishvili, K. (2021). Globalization and New Opportunities for Georgia. Globalization and Business. 12, 32-36. https:// doi.org/10.35945/gb.2021.12.003 86. Zoidze, G. (2021). Importance of Euro-Atlantic Integration: Democracy, Security and Economic Development. Three Seas Economic Journal, 2(3), 1-7. 87. Zoidze, G., Abuselidze, G., Veshapidze, S. (2023). Economic Vulnerability of Small Powers. Journal of Geography, Politics and Society, 13(3), 1-12 88. Zoidze, G., Veshapidze, S. (2022). The Modern Economy and Values. Cambridge Scholars Publishing. p. 125. 89. Zoidze, G., & Veshapidze, S. (2022). Transformation of economic policy priorities under COVID-19. Three Seas Economic Journal, 3(2), 35-43. 90. Zubiashvili, T., Veshapidze, Sh. (2019). Labor Emigration and Employment in Georgia. (Co-authorship). Humanities and Social Sciences Review, Volume 09, Number 01, USA. pp. 127-136. http://www.universitypublications. net/hssr/0901/html/E9X94.xml